2017
DOI: 10.1038/ajg.2017.5
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Nonalcoholic Steatohepatitis-Associated Cirrhosis in the United States: An Analysis of National Health and Nutrition Examination Survey Data

Abstract: There has been a 2.5-fold and 2-fold increases in the prevalence of NASH cirrhosis and NAFLD-associated advanced fibrosis, respectively, in 2009-2012 compared to 1999-2002. Extrapolation of NHANES data suggests that in 2010, 417,524 in the US had NASH cirrhosis, and 4,104,871 had NAFLD-associated advanced fibrosis. This represents a major disease burden and suggests the need for widespread programs to identify and treat those affected, and public health efforts aimed at controlling the burden of NAFLD and its … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
136
0
4

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 204 publications
(144 citation statements)
references
References 24 publications
4
136
0
4
Order By: Relevance
“…NASH with fibrosis) may reach up to more than 4 million of adult Americans. Of note, a recent study suggest that the prevalence of NASH-related cirrhosis and fibrotic NAFLD has increased 2.5-fold and 2-fold respectively in the U.S., which is in line with the observation that NASH-related cirrhosis is surpassing hepatitis C virus-related cirrhosis as the top etiology for adults listed for liver transplantation in that country (9). Thus, NASH-related cirrhosis is rising as a medical problem and, given the lack of awareness of NAFLD, it is likely that the real disease burden of this condition remains occult.…”
supporting
confidence: 73%
“…NASH with fibrosis) may reach up to more than 4 million of adult Americans. Of note, a recent study suggest that the prevalence of NASH-related cirrhosis and fibrotic NAFLD has increased 2.5-fold and 2-fold respectively in the U.S., which is in line with the observation that NASH-related cirrhosis is surpassing hepatitis C virus-related cirrhosis as the top etiology for adults listed for liver transplantation in that country (9). Thus, NASH-related cirrhosis is rising as a medical problem and, given the lack of awareness of NAFLD, it is likely that the real disease burden of this condition remains occult.…”
supporting
confidence: 73%
“…Recent data demonstrated that approximately 4.5 million people might have advanced fibrosis related to NASH in the United States. (10) Unfortunately, studies by our group and others have clearly shown that most patients with end-stage liver disease secondary to NASH had no previous diagnosis of liver disease. (11,12) This is related to the lack of clear guidance on whom to screen for NASH and how to do it in high-risk individuals.…”
Section: Challenge #1: Most Patients With Nash-associated Advanced Fimentioning
confidence: 84%
“…Owing to its generally asymptomatic nature and the lack of routine noninvasive screening tools, the true prevalence of NASH is unknown, but it is estimated to be between 1.5% and 6.5% globally . Patients with NASH—especially those with advanced fibrosis—have an increased risk for progression to cirrhosis, hepatic decompensation, and hepatocellular carcinoma (HCC) . NASH is projected to become the leading indication for liver transplantation in the near future …”
mentioning
confidence: 99%